2009
DOI: 10.1021/ef8008597
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solvent−Bitumen−Water Rag Layers

Abstract: A major operational issue in the crude oil industry is the formation of intermediate rag layers, (primarily water-in-oil emulsions) in oil−water separation processes that limit the amount and quality of recoverable oil. In this study, the formation of rag layers is evaluated as a function of solvent−bitumen−water ratios, solvent aromaticity, and temperature, with various imaging techniques. Using these techniques, it is possible to obtain an estimate of the amount of oil, water, and asphalthenes in the rag lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 44 publications
(63 reference statements)
5
64
0
Order By: Relevance
“…In the worst case the presence of this densely packed layer can completely stop the oil-water separation process. 6,15 The rheological study of interfacial asphaltene films by harmonic volume oscillations of a pendant drop has shown that the dilatational elasticity dominates the interfacial microstructure with only a small viscous contribution. 16,17,18 Such rheological characteristic has been observed over a wide range of asphaltene concentrations and extensive aging time, with emulsion stability at equivalent asphaltene concentrations being qualitatively linked to rheological properties of the interfacial film.…”
Section: Introductionmentioning
confidence: 99%
“…In the worst case the presence of this densely packed layer can completely stop the oil-water separation process. 6,15 The rheological study of interfacial asphaltene films by harmonic volume oscillations of a pendant drop has shown that the dilatational elasticity dominates the interfacial microstructure with only a small viscous contribution. 16,17,18 Such rheological characteristic has been observed over a wide range of asphaltene concentrations and extensive aging time, with emulsion stability at equivalent asphaltene concentrations being qualitatively linked to rheological properties of the interfacial film.…”
Section: Introductionmentioning
confidence: 99%
“…13 The attached clays to the bitumen surface can also cause problems in bitumen froth treatment by forming a rag layer. [14][15][16] The mechanism for bitumen slime coating has recently been studied in detail by Masliyah et al using atomic force microscopy (AFM) and zeta potential distribution measurement. 12,[17][18][19][20][21][22][23] While oil sands ores are a complex mixture of clays including kaolinite, illite, chlorite, montmorillonite, not all the clays cause slime coating.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] In oil production, the formation of a complex multiphase dispersion layer in the middle of oil-water separation vessel, known as rag layers, is frequently encountered. 21,22 The rag layers are extremely stable multiemulsions with the stabilizing species identified as surfactants, asphaltenes and inorganic fine particles. The inorganic fine particles are predominantly iron-containing solids that readily associate with organic compounds such as asphaltenes to form biwettable solids which preferentially stabilize w/o emulsions.…”
Section: Introductionmentioning
confidence: 99%